2007
DOI: 10.1016/j.aquatox.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatic glutathione S-transferases in coho salmon (Oncorhynchus kisutch)

Abstract: The glutathione S-transferases (GSTs) are a family of phase II detoxification enzymes which protect against chemical injury. In contrast to mammals, GST expression in fish has not been extensively characterized, especially in the context of detoxifying waterborne pollutants. In the Northwestern United States, coho salmon (Oncorhynchus kisutch) are an important species of Pacific salmon with complex life histories that can include exposure to a variety of compounds including GST substrates. In the present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Glutathione S-transferases (GSTs) are a family of phase II enzymes that have been shown to play an important role in the disposition of a wide range of environmental chemicals, pesticides and other reactive intermediates [10]. GST primarily catalyses the conjugation of electrophilic compounds with the thiol group of reduced glutathione (GSH), generally making the resultant products more water soluble and extractable than the non-GSH conjugated substrates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S-transferases (GSTs) are a family of phase II enzymes that have been shown to play an important role in the disposition of a wide range of environmental chemicals, pesticides and other reactive intermediates [10]. GST primarily catalyses the conjugation of electrophilic compounds with the thiol group of reduced glutathione (GSH), generally making the resultant products more water soluble and extractable than the non-GSH conjugated substrates [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Trute et al (2007) reported a complex glutathione S-transferase isoenzyme profile in coho salmon (Oncorhynchus kisutch), a sensitive and economically important salmonid species in the Pacific Northwest. The current study was initiated to characterize the expression of Phase I biotransformation enzymes in coho.…”
Section: Introductionmentioning
confidence: 99%
“…Some classes of GSTs were found in several fish species (Leaver et al, 1997;Melgar Riol et al, 2001;Doi et al, 2004;Lee et al, 2005;Konishi et al, 2005b;Fan et al, 2007;Trute et al, 2007). A distinct GST isoform, which has no homologues in mammals, was found in fish and named as rho class in red sea bream (Pagrus major) (Konishi et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%